2001
DOI: 10.1002/bem.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5 s exposures to a 50 μT, 20 Hz magnetic field on skin conductance and ratings of affect and arousal

Abstract: This study investigated the effect of a weak magnetic field (50 microT, 20 Hz sinusoidal, 5 s duration) on concurrent perceptions of visual stimuli. Subjects were seated between Helmholtz coils and gave post-exposure ratings for the affective content and arousing nature of presented images. They were blind as to the presence or absence of a simultaneously presented field. Skin conductance and arousal ratings did not show significant differences between experimental and control conditions, but the affective con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…These results provide some support for the controversial theory that the presence of certain types of local magnetic elds may impact upon a range of psychological, psychophysiological and health-related variables (Korinevskaya, Kholodov, & Korinevskii, 1993;Voustianiouk & Kaufmann, 2000). A controlled laboratory study by Stevens (2001), for instance, showed psychological and physiological reactions to a changing magnetic eld of comparable magnitude to those measured in our two experimental venues. Even subtle psychological and physiological changes occurring in a context that might suggest paranormal events (e.g.…”
Section: An Investigation Into Alleged 'Hauntings' 207supporting
confidence: 82%
“…These results provide some support for the controversial theory that the presence of certain types of local magnetic elds may impact upon a range of psychological, psychophysiological and health-related variables (Korinevskaya, Kholodov, & Korinevskii, 1993;Voustianiouk & Kaufmann, 2000). A controlled laboratory study by Stevens (2001), for instance, showed psychological and physiological reactions to a changing magnetic eld of comparable magnitude to those measured in our two experimental venues. Even subtle psychological and physiological changes occurring in a context that might suggest paranormal events (e.g.…”
Section: An Investigation Into Alleged 'Hauntings' 207supporting
confidence: 82%
“…Moreover, since we did not investigated other elements of cognitive performance function, such as vigilance, attention, memory and intelligence ; Graham et al Gamberale et al (1989) 50-Hz EF+MF 3 kV/m+23 lT Visual (color-word) No Cook et al (1992) 60-Hz EF+MF 9kV/m+20 lT Visual (three lights) No (but accuracy increased) Whittington et al (1996) 50-Hz MF 100 lT Visual (two flashes) No (in easy task), and decrease (in difficult task) Preece et al (1998) 50-Hz MF 600 lT Visual (two words) No Crasson et al (1999) 50 Gamberale et al (1989) 50-Hz EF+MF 3 kV/m+23 lT Visual No Cook et al (1992) 60-Hz EF+MF 9 kV/m+20 lT Auditory and visual No Graham et al (1994) 60-Hz EF+MF (1) 6 kV/m+10 lT Auditory and visual (1) Increase (2) 9 kV/m+20 lT (2) No (3) 12 kV/m+30 lT (3) No Lyskov et al (1993) 45-Hz MF 1,260 lT Auditory No Podd et al (1995) 0.2-Hz MF 1,100 lT Visual No Preece et al (1998) 50-Hz MF 600 lT Visual No Crasson et al (1999) 50-Hz MF 100 lT Auditory No This study 50-Hz MF 20 lT Auditory and visual No 1994;Stevens 2001), further research with a wide spectrum of brain-function test batteries is desired.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, only Stevens [2001] has addressed how individual differences in responsivity to a MF may exist. He noted that subjects could be grouped based on their skin conductance responses (a measure of arousal) to a 50 Hz ELF MF, finding ''high,'' ''low,'' and ''no'' responders to the field.…”
Section: Discussionmentioning
confidence: 98%